Community Education regarding the Distribution of Inheritance Assets in Kading Village, Awangpone District, Bone Regency - Alwi Jaya; Gustika Sandra; Tarmizi (Publikasi Indonesia, 2021)
Legal counseling activities as a form of community service which is the flagship program of Watampone Pengayoman College of Law aims to educate and solve problems in society. In this case, the legal counseling carried out in Kading Village, Awangpone District, Bone Regency is related to education on the distribution of inheritance and aims to increase the community's insight regarding procedures for dividing inheritance. The method used in this service activity is legal counseling by providing material related to the rules for dividing inheritance and followed by discussion. The results of this activity show that the people of Kading Village have better knowledge about the procedures for distributing inheritance assets according to the regulations in force in Indonesia. This activity provides progressive benefits and helps the community understand the procedures for distributing inheritance assets in accordance with applicable law and increases people's insight so that they are wise in dividing inheritance assets as an effort to avoid disputes due to competition over inheritance assets.